Preparation method of ultraviolet-resistant long-corrosion-resistant composite epoxy coating
The two-dimensional sheet composite material modified by metal organic frame solves the aging problem of water-based epoxy coating in high salt, wet and strong UV environments, improves the UV aging resistance and corrosion resistance of the coating, and extends the The service life of marine equipment.
Patent Information
- Application Number
- CN202411577921.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The existing water-based epoxy coating is prone to holes and cracks under high salt, high humidity and strong ultraviolet radiation environments, resulting in accelerated penetration of corrosive media, reducing the service life of the equipment, and the anti-UV aging agent is incompatible with epoxy resin, which affects the Comprehensive protective properties of the coating.
Two-dimensional sheet composite material modified with metal organic frames forms a porous topological structure through chemical coordination, and loads anti-UV aging agent to improve the compatibility of fillers and resins and the anti-UV aging properties of coatings, reducing internal defects and Pores, enhance physical barrier performance.
It significantly improves the UV aging resistance and long-term corrosion resistance of the coating, extends the service life of marine equipment, avoids direct contact between anti-UV aging agent and epoxy resin, and ensures the structural integrity and protection of the coating. performance.
Smart Images

Figure CN119220153A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of corrosion and protective coatings, and in particular relates to a method for preparing an ultraviolet-resistant and long-corrosion-resistant composite epoxy coating. Background Art
[0002] The development and utilization of various marine resources is the cornerstone of the rapid development of the national marine economy. Among them, the long-term and stable service of marine engineering equipment and ships is the guarantee of marine resource development. Taking the South China Sea environment as an example, marine engineering equipment has been in service for a long time in a harsh environment of high salt, high humidity, high temperature and strong ultraviolet radiation. Corrosion and its coupled damage are one of the main factors that shorten its life and cause safety accidents. Practice has proved that organic coating is one of the most important technologies to protect marine engineering equipment and extend its service life. Among them, water-based epoxy coating is environmentally friendly and has excellent corrosion resistance, and has been widely used in the protection of marine engineering equipment. However, during the curing and service process, holes and cracks will appear in the coating. At the same time, under strong sunlight, ultraviolet radiation will destroy the internal structure of the coating through photo-oxidation reaction, significantly accelerating the aging of the coating. In this case, the penetration of corrosive media will accelerate the degradation of metal properties, thereby shortening the service life of the equipment. Therefore, how to reduce the internal defects of the coating while improving its anti-ultraviolet aging performance, thereby extending the service life of marine engineering equipment is a scientific and technological problem that technicians in the field of corrosion and protection need to solve urgently.
[0003] In response to the problem of insufficient UV aging resistance of epoxy coatings, the existing solution is usually to add UV aging agents directly to the coating resin. However, not all UV aging agents have good compatibility with epoxy resins, so directly adding UV aging agents may destroy the integrity of the internal structure of the coating, resulting in a decrease in the overall protective performance of the coating. Among them, two-dimensional sheets are widely used to reduce internal defects in coatings and block the penetration of corrosive media. However, most two-dimensional sheets are inorganic substances, which are incompatible with organic resins. There are weak areas at the filler / resin interface, and they do not have the ability to improve the UV aging resistance of the coating. Therefore, if the compatibility of the filler and the resin and the UV aging resistance of the coating can be improved at the same time, it is expected that the service life of the coating can be greatly extended. Summary of the invention
[0004] In order to overcome the shortcomings of the above-mentioned prior art, the present invention provides a method for preparing an anti-UV and long-term corrosion-resistant composite epoxy coating. The epoxy coating prepared by this method can greatly improve the compatibility between the filler and the resin, reduce the internal defects of the coating, and enhance the anti-UV aging performance and long-term corrosion resistance of the coating, and has important application prospects in the field of corrosion and protection of marine engineering equipment.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] The first aspect of the present invention provides a method for preparing an ultraviolet-resistant and long-corrosion-resistant composite epoxy coating, the method comprising the following steps:
[0007] S1. Preparation of metal organic framework loaded with anti-ultraviolet aging agent modified two-dimensional sheet composite material:
[0008] S11, dispersing the two-dimensional sheet in water, adding metal salt and organic ligand, stirring to form a yellow turbid liquid, separating and collecting the yellow solid, washing and drying to obtain a yellow powdery metal-organic framework modified two-dimensional sheet nanomaterial;
[0009] S12, dispersing the two-dimensional sheet nanomaterial of S11 in a solvent, adding an anti-ultraviolet aging agent, separating and collecting a light yellow solid after vacuum loading, and then washing and drying to obtain a light yellow powdery metal organic framework-loaded anti-ultraviolet aging agent-modified two-dimensional sheet composite material;
[0010] S2, composite material modified epoxy resin: epoxy resin emulsion, the two-dimensional sheet composite material prepared in step S1 and a diluent are mixed, and then a curing agent is added, and the mixture is continued to be mixed to obtain a modified epoxy resin;
[0011] S3, coating: coating the modified epoxy resin obtained in step S2 on the surface of the metal substrate, and after drying and curing, an anti-ultraviolet and long-corrosion resistant composite epoxy coating (i.e., a two-dimensional sheet composite material modified epoxy coating modified by a metal organic framework-loaded anti-ultraviolet aging agent) is obtained on the surface of the metal substrate.
[0012] Metal organic framework is a crystalline material with a porous topological structure formed by chemical coordination of metal ions and organic ligands under certain conditions. The present invention prepares a metal organic framework loaded with an anti-ultraviolet aging agent modified two-dimensional sheet composite material through two-dimensional sheets, metal salts, organic ligands and anti-ultraviolet aging agents, wherein the two-dimensional sheets are derived from industrial preparation and have reliable quality; the organic ligands have the advantages of diversity, and the size, quantity and pore size of the metal organic framework can be regulated by changing the type and addition amount of the organic ligands. For example, the organic ligands containing benzene rings have large steric hindrance, so the prepared metal organic framework is larger in size and has more porosity, which can increase the loading amount of the anti-ultraviolet aging agent. Adding it as a filler to epoxy resin can improve the compatibility of the two-dimensional sheet with epoxy resin, enhance the physical barrier properties of the coating, and then reduce the internal defects of the coating and improve its anti-ultraviolet aging performance. At the same time, since the organic ligands of the metal organic framework in the composite material contain imidazole rings and carboxyl / amino groups, the compatibility of the composite material and epoxy resin is increased, and the dispersibility of the composite material is improved, the pores in the coating curing process are filled, the density and cross-linking density of the coating are improved, and the time for the corrosive medium to reach the metal surface is prolonged, ultimately increasing the long-term corrosion resistance of the coating.
[0013] Preferably, the two-dimensional sheet in S11 includes at least one of graphene, graphene oxide, reduced graphene oxide, hexagonal boron nitride, black phosphorus sheet, and transition metal sulfide.
[0014] Preferably, the metal salt in S11 is at least one of cerium nitrate, cerium chloride, cerium sulfate, ammonium cerium nitrate or cerium acetate.
[0015] Preferably, the organic ligand in S11 is at least one of butynedioic acid, imidazole, 2-methylimidazole, benzimidazole, 2-aminobenzimidazole, terephthalic acid, and 2-aminoterephthalic acid.
[0016] Preferably, the anti-ultraviolet aging agent described in S12 is at least one of benzotriazole, phenyl salicylate, 2,2,6,6-tetramethylpiperidine and 3-[3-(2-H-benzotriazole-2-yl)-4-hydroxy-5-tert-butylphenyl]-propionic acid-polyethylene glycol 300 ester (UV-1130).
[0017] Preferably, the mass ratio of the two-dimensional sheet, metal salt and organic ligand in S1 is 0.1-0.5:1-3:0.5-2, and the mass ratio of the metal organic framework modified two-dimensional sheet nanomaterial and the anti-ultraviolet aging agent is 0.1:0.1-1.
[0018] By adjusting the mass ratio of the two-dimensional sheet and the metal salt to the organic ligand, the coverage of the metal organic framework on the two-dimensional sheet can be controlled, and the size and number of the metal organic framework can also be controlled, thereby improving the dispersibility of the composite material in the epoxy resin. At the same time, by changing the amount of anti-ultraviolet aging agent added, the loading amount of the anti-ultraviolet aging agent in the composite material can be increased, thereby enhancing the anti-ultraviolet aging performance of the coating. Under the above mass ratio, the metal organic framework can fully cover the surface of the two-dimensional sheet, ensuring that the size of the metal organic framework is between 100 and 2000 nm, and the loading amount of the anti-ultraviolet aging agent reaches 10 to 30 wt.%.
[0019] Preferably, the vacuum load time in S12 is 10 to 24 hours.
[0020] Preferably, the mass ratio of the epoxy emulsion, the two-dimensional sheet composite material and the diluent in S2 is 12:0.12~2.4:2~12.
[0021] Preferably, the thickness of the UV-resistant and corrosion-resistant composite epoxy coating obtained by S3 on the surface of the metal substrate is 30 to 200 μm.
[0022] Preferably, the diluent described in S2 is a mixture of anhydrous ethanol and deionized water, and the mass ratio of ethanol to deionized water is 1:5.
[0023] The introduction of diluent can improve the dispersion of filler in resin, reduce the viscosity of coating, and facilitate coating coating and leveling.
[0024] Preferably, the curing agent described in S2 is diethylenetriamine or triethylenetetramine.
[0025] According to the empirical value reference given by the coating supplier, the amount of curing agent used is 50% of the epoxy emulsion. However, in the actual construction process, the coating will be appropriately diluted, and in order to ensure that the epoxy resin is completely cured, the curing agent dosage will be excessive by 10-20wt.%. The curing agent used in the present invention can be cured at room temperature, thereby increasing the operability of the coating.
[0026] Preferably, the metal substrate described in S3 is one of carbon steel, aluminum alloy, titanium alloy, magnesium alloy and copper alloy.
[0027] Preferably, the drying and curing temperature in S3 is 25° C. to 60° C., and the curing time is 24 h to 72 h.
[0028] The second aspect of the present invention provides an anti-ultraviolet and long-corrosion resistant composite epoxy coating prepared by the preparation method described in the first aspect.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] Although the two-dimensional sheet can improve the physical barrier properties of the coating through large specific surface area, anti-penetration and "maze effect", the sheet has poor compatibility with the resin interface, which easily causes the coating to fail. In addition to being incompatible with the resin, the addition of only an anti-ultraviolet aging agent may also directly react with the resin, thereby reducing the comprehensive performance of the coating or making it difficult to achieve the effect of improving the anti-ultraviolet performance. To this end, the present invention has developed a two-dimensional sheet composite material, which uses a metal organic framework to modify the two-dimensional sheet material, thereby improving the compatibility of the sheet with the epoxy resin and filling the defects inside the coating. At the same time, the anti-ultraviolet aging agent is loaded in the metal organic framework to avoid direct contact with the epoxy resin, ensure the structural integrity of the anti-ultraviolet aging agent, and finally make the modified epoxy coating show excellent anti-ultraviolet aging performance and long-term corrosion resistance. In addition, the present invention can control the number and size of the metal organic framework on the surface of the two-dimensional sheet by regulating the two-dimensional sheet and the dosage ratio of the metal salt and the organic ligand, and can regulate the coverage of the metal organic framework on the surface of the two-dimensional sheet within a certain range, thereby improving the physical barrier properties of the coating. Furthermore, the loading amount of the anti-ultraviolet aging agent in the composite material can be increased by regulating the porosity of the metal organic framework and the amount of anti-ultraviolet aging agent added, thereby further improving the anti-ultraviolet aging performance of the coating while ensuring the physical barrier performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1The morphology, structure and element distribution of GO-HHU-T;
[0032] Figure 2 The cross-sectional morphology of the coatings prepared in Example 1 and Comparative Example 1 after being brittle fractured with liquid nitrogen;
[0033] Figure 3 Electrochemical impedance spectroscopy of the coatings prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0034] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0035] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0036] Example 1
[0037] (1) Preparation of Ce-based Metal-Organic Framework-loaded UV-1130-modified Graphene Oxide Composites (GO-HHU-T):
[0038] 0.25 g of graphene oxide was ultrasonically dispersed in 30 mL of deionized water, and 1.5 g of ammonium cerium nitrate and 1.25 g of butynedioic acid were added. The mixture was stirred at room temperature for 14 h on a magnetic stirrer to obtain a yellow turbid liquid. The solution was then centrifuged and washed alternately with anhydrous ethanol and deionized water for 4 times to obtain a yellow solid. The solid was finally dried in a vacuum drying oven at 60 °C for 17 h to obtain a yellow powdery GO-HHU.
[0039] 0.1 g of the above GO-HHU powder was ultrasonically dispersed in 20 mL of anhydrous ethanol, and then 0.5 g of UV-1130 anti-ultraviolet aging agent was added, and the mixture was placed in a drying oven under vacuum load for 17 h (temperature 25 ° C, vacuum degree -0.1 MPa), followed by centrifugation, and then washed with anhydrous ethanol for 4 times to obtain a light yellow solid, which was finally placed in a vacuum drying oven at 60 ° C for 24 h to obtain a light yellow powder GO-HHU-T;
[0040] (2) Preparation of composite material modified epoxy resin:
[0041] The epoxy emulsion, GO-HHU-T and diluent in a mass ratio of 12:0.2:2 were mixed, wherein the diluent was anhydrous ethanol and deionized water in a mass ratio of 1:5, and after magnetic stirring for 20 minutes, 65wt.% of the emulsion mass of the curing agent diethylenetriamine was added, stirred for 20 minutes, and the composite material modified epoxy resin was obtained after mixing.
[0042] (3) Coating film:
[0043] The composite material modified epoxy resin obtained in step (2) was coated on the surface of a treated carbon steel substrate (polished from 220 mesh to 1000 mesh, then ultrasonically cleaned with anhydrous ethanol to remove surface oil and impurities, and finally the sample surface was blown dry with a cold air blower). After drying and curing at 25°C, a GO-HHU-T composite material modified epoxy coating was obtained on the carbon steel surface. The dry paint film thickness of the composite coating was 50±5 μm.
[0044] Comparative Example 1
[0045] In this embodiment, epoxy emulsion and diluent with a mass ratio of 12:2 are directly mixed, wherein the diluent is anhydrous ethanol and deionized water with a mass ratio of 1:5, and after magnetic stirring for 20 minutes, 65wt.% of the emulsion mass of curing agent diethylenetriamine is added, stirred for 20 minutes, and the epoxy resin coating is obtained after mixing. The epoxy resin is coated on the surface of the treated carbon steel substrate, and after drying and curing, an epoxy coating is obtained on the carbon steel surface, and the dry paint film thickness of the epoxy coating is 50±5μm.
[0046] Morphology characterization and performance testing of Example 1 and Comparative Example 1:
[0047] (1) Composite material microstructure test
[0048] The prepared GO-HHU-T was observed under a transmission electron microscope, and the morphology, structure and element distribution were as follows: Figure 1 As shown, it can be seen that HHU achieves uniform growth on the GO surface, which reduces the aggregation and wrinkling of GO itself, and UV-1130 is also successfully loaded into HHU.
[0049] (2) Coating cross-sectional morphology test
[0050] The coatings prepared in Example 1 and Comparative Example 1 were fractured with liquid nitrogen and their cross-sectional morphologies were observed using a scanning electron microscope. Figure 2 As shown in the figure, it can be seen that the cross-sectional morphology of comparative example 1 is smooth, showing obvious brittle fracture properties, and there are clear defects and holes; while the cross-sectional morphology of embodiment 1 is rough, with obvious ductile fracture characteristics, and no defects and holes are found, indicating that the GO-HHU-T composite material can fill the defects inside the epoxy coating and improve its density and mechanical properties.
[0051] (3) Electrochemical impedance spectroscopy experiment of coating after UV aging
[0052] The coatings prepared in Example 1 and Comparative Example 1 were subjected to continuous accelerated aging for 168 h using a UVB lamp (313 nm, 60 W) according to ISO16474-2021 standard; the coatings prepared in Example 1 and Comparative Example 1 after UV aging were then placed in a 3.5 wt.% sodium chloride solution for electrochemical testing. After 100 days of electrochemical testing, the impedance modulus results were as follows: Figure 3 As shown, the low-frequency impedance modulus of Example 1 is always maintained at 10 9 ~10 11 Ω·cm 2 , while the low-frequency impedance modulus of comparative example 1 is always maintained at 10 5 ~10 8 Ω·cm 2 , indicating that the corrosion resistance of the epoxy coating modified by GO-HHU-T composite material is improved by 3 orders of magnitude compared with that of the pure epoxy coating, indicating that the epoxy coating modified by GO-HHU-T composite material has good anti-ultraviolet aging performance and long-term corrosion resistance.
[0053] Example 2
[0054] (1) Preparation of cerium-based metal organic framework loaded with benzotriazole-modified hexagonal boron nitride composite material (hBN-CeMOF-BTA):
[0055] 0.3 g of hexagonal boron nitride was ultrasonically dispersed in 30 mL of deionized water solution, and then 2 g of ammonium cerium nitrate and 1.5 g of terephthalic acid were added. The mixture was stirred at room temperature for 24 h on a magnetic stirrer to obtain a gray turbid liquid. The solution was then centrifuged and washed alternately with anhydrous ethanol and deionized water for 4 times to obtain a gray solid. Finally, the solid was placed in a vacuum drying oven and dried at 50 °C for 12 h to obtain a gray powdered hBN-CeMOF.
[0056] 0.1 g of the hBN-CeMOF powder was ultrasonically dispersed in 20 mL of anhydrous ethanol, and 0.6 g of an anti-ultraviolet aging agent BTA was added, and the mixture was placed in a drying oven under vacuum load for 15 h, followed by centrifugation, and then washed with anhydrous ethanol for 4 times to obtain a light gray solid, which was finally placed in a vacuum drying oven and dried at 50 ° C for 12 h to obtain a light gray powdered hBN-CeMOF-BTA;
[0057] (2) Preparation of composite material modified epoxy resin:
[0058] Epoxy emulsion, hBN-CeMOF-BTA and diluent in a mass ratio of 12:0.15:2.5 were mixed, wherein the diluent was anhydrous ethanol and deionized water in a mass ratio of 1:5, and after magnetic stirring for 20 minutes, 55 wt.% of the emulsion mass of curing agent triethylenetetramine was added, stirred for 20 minutes, and mixed to obtain a composite material modified epoxy resin.
[0059] (3) Coating film:
[0060] The composite material modified epoxy resin obtained in step (2) is coated on the treated surface of the copper alloy substrate. After drying and curing, an hBN-CeMOF-BTA composite material modified epoxy coating is obtained on the copper alloy surface. The dry film thickness of the composite coating is 80±10 μm.
[0061] The coating cross-sectional morphology test and the electrochemical impedance spectroscopy experiment of the coating after UV aging were carried out according to the method of Example 1. The cross-sectional morphology of the hBN-CeMOF-BTA composite modified epoxy coating of this example was rough, with tough fracture, and no obvious defects were observed. Its low-frequency impedance value was maintained at 10 9 ~10 11 Ω·cm 2 , indicating that the hBN-CeMOF-BTA composite material can effectively reduce the internal defects of the epoxy coating and exhibit stable long-term corrosion resistance.
[0062] Example 3
[0063] (1) Preparation of aminated cerium-based metal organic framework loaded with phenyl salicylate-modified black phosphorus composite material (BP-NH2CeMOF-PS):
[0064] 0.15 g of black phosphorus was ultrasonically dispersed in 30 mL of deionized water solution, and then 2.5 g of ammonium cerium nitrate and 1 g of aminoterephthalic acid were added. The mixture was stirred at room temperature for 20 h on a magnetic stirrer to obtain a gray turbid liquid. The solution was then centrifuged and washed alternately with anhydrous ethanol and deionized water for 4 times to obtain a gray solid. Finally, the solid was placed in a vacuum drying oven and dried at 70 °C for 10 h to obtain a gray powdered BP-NH2CeMOF.
[0065] 0.1 g of the above BP-NH2CeMOF powder was ultrasonically dispersed in 20 mL of anhydrous ethanol, and then 0.4 g of anti-ultraviolet aging agent PS was added, and the mixture was placed in a drying oven under vacuum load for 20 h, followed by centrifugation, and then washed with anhydrous ethanol for 4 times to obtain a light gray solid, which was finally placed in a vacuum drying oven and dried at 40 ° C for 24 h to obtain a light gray powdery BP-NH2CeMOF-PS;
[0066] (2) Preparation of composite material modified epoxy resin:
[0067] The epoxy emulsion, BP-NH2CeMOF-PS and diluent in a mass ratio of 12:1.2:3 were mixed, wherein the diluent was anhydrous ethanol and deionized water in a mass ratio of 1:5, and after magnetic stirring for 20 minutes, 60wt.% of the emulsion mass of the curing agent diethylenetriamine was added, stirred for 20 minutes, and mixed to obtain a composite material modified epoxy resin.
[0068] (3) Coating film:
[0069] The composite material modified epoxy resin obtained in step (2) is coated on the treated surface of the aluminum alloy substrate. After drying and curing, a BP-NH2CeMOF-PS composite material modified epoxy coating is obtained on the aluminum alloy surface. The dry film thickness of the composite coating is 100±10 μm.
[0070] The coating cross-sectional morphology test and the electrochemical impedance spectroscopy experiment of the coating after UV aging were carried out according to the method of Example 1. The cross-sectional morphology of the BP-NH2CeMOF-PS composite modified epoxy coating of this example was rough, with tough fracture, and no obvious defects were observed. Its low-frequency impedance value was maintained at 10 9 ~10 11 Ω·cm 2 , indicating that the BP-NH2CeMOF-PS composite material can fill the internal defects of the epoxy coating to a great extent and exhibit good long-term corrosion resistance.
[0071] Example 4
[0072] (1) Preparation of cerium-based metal organic framework loaded with 2,2.6.6-tetramethylpiperidine modified transition metal sulfide composite material (MoS2-CeMOF-TP):
[0073] 0.5 g of transition metal sulfide (MoS2) was ultrasonically dispersed in 30 mL of deionized water solution, and 3 g of cerium nitrate and 0.8 g of aminoterephthalic acid were added. The mixture was stirred at room temperature for 20 h on a magnetic stirrer to obtain a gray turbid liquid. The solution was then centrifuged and washed alternately with anhydrous ethanol and deionized water for 4 times to obtain a gray solid. The solid was finally dried in a vacuum drying oven at 70 °C for 10 h to obtain a gray powdered MoS2-CeMOF.
[0074] 0.1 g of the above MoS2-CeMOF powder was ultrasonically dispersed in 20 mL of anhydrous ethanol, and then 0.4 g of anti-ultraviolet aging agent TP was added, and the mixture was placed in a drying oven under vacuum load for 20 h, followed by centrifugation, and then washed with anhydrous ethanol for 4 times to obtain a light gray solid, which was finally placed in a vacuum drying oven and dried at 40 ° C for 24 h to obtain a light gray powdered MoS2-CeMOF-TP;
[0075] (2) Preparation of composite material modified epoxy resin:
[0076] Epoxy emulsion, MoS2-CeMOF-TP and diluent in a mass ratio of 12:1.2:4 were mixed, wherein the diluent was anhydrous ethanol and deionized water in a mass ratio of 1:5, and after magnetic stirring for 20 minutes, 60 wt.% of the emulsion mass of curing agent diethylenetriamine was added, stirred for 20 minutes, and mixed to obtain a composite material modified epoxy resin.
[0077] (3) Coating film:
[0078] The composite material modified epoxy resin obtained in step (2) is coated on the treated surface of the magnesium alloy substrate. After drying and curing, a MoS2-CeMOF-TP composite material modified epoxy coating is obtained on the magnesium alloy surface. The dry paint film thickness of the composite coating is 100±10μm.
[0079] The coating cross-sectional morphology test and the electrochemical impedance spectroscopy experiment of the coating after UV aging were carried out according to the method of Example 1. The cross-sectional morphology of the MoS2-CeMOF-TP composite material modified epoxy coating of this example was rough, with tough fracture, and no obvious defects were observed. Its low-frequency impedance value was maintained at 10 9 ~10 11 Ω·cm 2 , indicating that the MoS2-CeMOF-TP composite material can fill the internal defects of the epoxy coating to a great extent and exhibit good long-term corrosion resistance.
[0080] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A method for preparing an ultraviolet-resistant and long-corrosion-resistant composite epoxy coating, characterized in that: The following steps are involved: S1. Preparation of metal organic framework loaded with anti-ultraviolet aging agent modified two-dimensional sheet composite material: S11, dispersing the two-dimensional sheet in water, adding metal salt and organic ligand, stirring to form a yellow turbid liquid, separating and collecting the yellow solid, washing and drying to obtain a yellow powdery metal-organic framework modified two-dimensional sheet nanomaterial; S12, dispersing the two-dimensional sheet nanomaterial of S11 in a solvent, adding an anti-ultraviolet aging agent, separating and collecting a light yellow solid after vacuum loading, and then washing and drying to obtain a light yellow powdery metal organic framework-loaded anti-ultraviolet aging agent-modified two-dimensional sheet composite material; S2, composite material modified epoxy resin: epoxy resin emulsion, the two-dimensional sheet composite material prepared in step S1 and a diluent are mixed, and then a curing agent is added, and the mixture is continued to be mixed to obtain a modified epoxy resin; S3, coating: coating the modified epoxy resin obtained in step S2 on the surface of the metal substrate, and after drying and curing, a UV-resistant and long-corrosion-resistant composite epoxy coating is obtained on the surface of the metal substrate.
2. The method for preparing a UV-resistant and corrosion-resistant composite epoxy coating according to claim 1, characterized in that: S11 The two-dimensional sheet includes at least one of graphene, graphene oxide, reduced graphene oxide, hexagonal boron nitride, black phosphorus sheet, and transition metal sulfide.
3. The method for preparing a UV-resistant and corrosion-resistant composite epoxy coating according to claim 1, characterized in that: S11 The metal salt is at least one of cerium nitrate, cerium chloride, cerium sulfate, ammonium cerium nitrate or cerium acetate.
4. The method for preparing a UV-resistant and corrosion-resistant composite epoxy coating according to claim 1, characterized in that: The organic ligand in S11 is at least one of butynedioic acid, imidazole, 2-methylimidazole, benzimidazole, 2-aminobenzimidazole, terephthalic acid, and 2-aminoterephthalic acid.
5. The method for preparing a UV-resistant and corrosion-resistant composite epoxy coating according to claim 1, characterized in that: The anti-ultraviolet aging agent described in S12 is at least one of benzotriazole, phenyl salicylate, 2,2,6,6-tetramethylpiperidine and 3-[3-(2-H-benzotriazole-2-yl)-4-hydroxy-5-tert-butylphenyl]-propionic acid-polyethylene glycol 300 ester.
6. The method for preparing a UV-resistant and corrosion-resistant composite epoxy coating according to claim 1, characterized in that: The mass ratio of the two-dimensional sheet material, metal salt and organic ligand described in S1 is 0.1-0.5:1-3:0.5-2, and the mass ratio of the two-dimensional sheet nanomaterial modified by the metal organic framework and the anti-ultraviolet aging agent is 0.1:0.1-1.
7. The method for preparing a UV-resistant and corrosion-resistant composite epoxy coating according to claim 1, characterized in that: The vacuum load time in S12 is 10 to 24 hours.
8. The method for preparing a UV-resistant and corrosion-resistant composite epoxy coating according to claim 1, characterized in that: The mass ratio of the epoxy emulsion, the two-dimensional sheet composite material and the diluent in S2 is 12:0.12~2.4:2~12.
9. The method for preparing a UV-resistant and corrosion-resistant composite epoxy coating according to claim 1, characterized in that: The thickness of the UV-resistant and corrosion-resistant composite epoxy coating obtained by S3 on the surface of the metal substrate is 30 to 200 μm.
10. An anti-ultraviolet and long-corrosion resistant composite epoxy coating prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Cerium ion-loaded two-dimensional nano material-based self-healing barrier bifunctional coating as well as preparation method and application thereof
CN113150640A
Bio-based epoxy composite coating with intelligent controllable corrosion inhibition effect as well as preparation method and application of bio-based epoxy composite coating
CN114836107A
Composite ZIF modified multifunctional coating and preparation method thereof
CN118685096A
Cited By
Wear-resistant durable fastener and processing technology thereof
CN120290078A